Utility of automated cell counter histogram in diagnosis of thrombocytopenia and pseudothrombocytopenia - Hariom Meena,; Suresh Kumar Sutrakar,; Rifat Q Usmani,; Rashmi Jain,; Aayushi Guru,; Rakesh Gupta,; Vinod Kumar Shakya,; Parul Singh Rajput,; Shambhavi Sharma, (Asian Journal of Medical Sciences, 2023)
Background: Automated hematology analyzers have become mainstream of complete blood count (CBC) during the past two decades; they are potential, more accurate to produce results of CBCs. However, often automated analyzers can give false results too, specially, falsely low platelet count due to platelets aggregates, which have to be confirmed on peripheral smears. Aims and Objectives: The aim and objective of the study was to diagnose thrombocytopenia (TCP) cases and differentiate them from pseudothrombocytopenia (PTCP) cases by analyzing platelet histogram and to determine the sensitivity and specificity of platelet histograms for diagnosing TCP and PTCP. Materials and Methods: The present study was conducted in the Department of Pathology at Shyam Shah Medical College, Rewa, M.P., after obtaining ethical clearance from the Institutional Ethics Committee. It was prospective study conducted for a period of 15 months from January 2021 to May 2022 on 1000 samples. Results: The sensitivity and specificity of platelet histogram flags and presence of multiple peaks to diagnose TCP and PTCP cases were calculated as 73.60% and 93.60%, respectively. The present study also interpret that mean platelet volume and platelet distribution width cannot use as indicator to differentiate between TCP and PTCP. Conclusion: The present study concludes that analysis and interpretation of histogram more specifically platelet histogram flagging provide clue for early detection of PTCP cases prior peripheral smear examination and also helpful in differentiating them from true TCP cases. These platelet histogram flagging can be used as a screening parameter for the detection of PTCP and these are helpful in preventing unnecessary stress for clinician, patients, and their relatives. However, the peripheral smear examination will remain the gold standard to differentiate TCP from, PTCP.